SPG11: clinical and genetic features of seven Czech patients and literature review. (4th May 2022) - Doleckova, Kristyna; Roth, Jan; Stellmachova, Julia; Gescheidt, Tomas; Sigut, Vladimir; Houska, Pavel; Jech, Robert; Zech, Michael; Vyhnalek, Martin; Vyhnalkova, Emilie; Seeman, Pavel; Meszarosova, Anna Uhrova
ABSTRACT: SPG11 is one of the most frequent autosomal recessively inherited types of hereditary spastic paraplegias (HSP or SPG). We describe the first seven patients from the Czech Republic with biallelic pathogenic variants in the SPG11. The typical HSP neurological findings are present in all the described patients in that the signs of a complicated phenotype develop slowly. The speed of disease progression, and the severity of gait impairment, was fast in all patients but the phenotype varied from patient to patient. Thin corpus callosum was not observed in two patients. Two Czech SPG11 patients had unusual late onset of disease and both were compound heterozygotes for the c.5381T>C variant. Therefore, we looked for a potential ralationship between the type of variant in the SPG11 gene and the age of disease onset. By reviewing all described SPG11 patients carrying at least one missense pathogenic variant in the SPG11 gene we did not found any relationship between the age of onset and the type of variant. Together twelve pathogenic variants, including gross deletions, were found in the SPG11 gene the Czech SPG11 patients, the c.3454-2A>G variant is novel.